First application of ultrasound-assisted thrombolysis for acute, submassive pulmonary embolism in a pregnant patient. Issue 1 (2017) - Kalathiya, Rohan; Conway, Brian D; Blair, John A; Paul, Jonathan; , Atman P Shah; Ismail, Mahmoud; Nathan, Sandeep
No abstract available